Discovering the magic. Issue 60 (October 2016) - Cetinelli, Selin
Abstract : Inspiring transformation at Unilever CMI in a Volatile, Uncertain, Complex and Ambiguous World In an increasingly fast‐paced environment with big data pouring in from all directions, using the word "tough" to describe the volatility, uncertainty, complexity and ambiguity of business context nowadays is probably an understatement. We are now faced with principles such as perseverance and well‐being as necessities in order to survive this VUCA world. So what does that mean for organisations and more importantly for functions like market research or consumer insight departments in how they operate and how they manage research? This article focuses on hos Unilever has managed to balance this with its consumer‐centricity and "insights engine".